3D Photo-Fabrication for Tissue Engineering and Drug Delivery. (March 2015) - Pereira, Rúben F.; Bártolo, Paulo J.
ABSTRACT: The most promising strategies in tissue engineering involve the integration of a triad of biomaterials, living cells, and biologically active molecules to engineer synthetic environments that closely mimic the healing milieu present in human tissues, and that stimulate tissue repair and regeneration. To be clinically effective, these environments must replicate, as closely as possible, the main characteristics of the native extracellular matrix (ECM) on a cellular and subcellular scale. Photo-fabrication techniques have already been used to generate 3D environments with precise architectures and heterogeneous composition, through a multi-layer procedure involving the selective photocrosslinking reaction of a light-sensitive prepolymer. Cells and therapeutic molecules can be included in the initial hydrogel precursor solution, and processed into 3D constructs. Recently, photo-fabrication has also been explored to dynamically modulate hydrogel features in real time, providing enhanced control of cell fate and delivery of bioactive compounds. This paper focuses on the use of 3D photo-fabrication techniques to produce advanced constructs for tissue regeneration and drug delivery applications. State-of-the-art photo-fabrication techniques are described, with emphasis on the operating principles and biofabrication strategies to create spatially controlled patterns of cells and bioactive factors. Considering its fast processing, spatiotemporal control, high resolution, and accuracy, photo-fabrication is assuming a critical role in the design of sophisticated 3D constructs. This technology is capable of providing appropriate environments for tissue regeneration, and regulating the spatiotemporal delivery of therapeutics.